Development of food seasoning using sub-standard fish cracker, pumpkin (Cucurbita moschata) and seaweed (Kappaphycus alvarezii) - J M Hoy; Mansoor Abdul Hamid; Mat Salleh Ayub; R Suratman; M M Effendi; A In`am (IOP Publishing, 2024)
The study focuses on sub-standard fish crackers (amplang) that do not meet quality standards but are sold at reduced prices which affecting business profitability. It aims to create a seasoning powder using sub-standard fish crackers, pumpkin (C. moschata), and seaweed (K. alvarezii). Six formulations with varying proportions of sub-standard fish cracker (55% and 65%), pumpkin powder (20%) and seaweed powder in proportions of 1.5%, 3%, and 4.5% were developed and evaluated for physicochemical properties and sensory acceptance. 65% addition of sub-standard fish cracker to the seasoning powder produced a brighter colour. Formulation (F5) with 65% sub-standard fish cracker and 3% seaweed powder obtained the highest acceptance. F5 exhibited improved nutritional quality with higher ash, protein and dietary fibre content compared to control. The seaweed powder also helped to improve the seasoning powder's mineral profile, which is low in sodium and high in potassium. An eight-week storage study on F5 showed stable properties throughout, including water activity, colour, peroxide value, free fatty acid and microbiological status. Overall, the study offers a strategic approach to enhance the utilization of sub-standard fish crackers, improving acceptability and nutritional value for consumers.